Beyond Doctrinal Exclusivism: Human Dignity and Diaconal Engagement as a Practical Theology for Social Cohesion in Indonesia - David Priyo Susilo; Kalis Stevanus; Yeremia Didasgil Taneo (Jurnal Theologia, 2026)
This study investigates how Christian Religious Education (Pendidikan Agama Kristen / PAK) lecturers in Indonesian higher education institutions facilitate interreligious dialogue to mitigate horizontal conflicts and nurture systemic tolerance. Employing a qualitative descriptive methodology grounded in a comprehensive literature review, this research systematically analyzes the transformation of pedagogical approaches from doctrinally exclusive models toward context-sensitive, dialogical frameworks. The findings reveal that academic actors serve as essential ethical and pedagogical agents by integrating interreligious dialogue into the curricula, facilitating structured interfaith discussions, modeling inclusive behavior, and leading cross-faith institutional partnerships. The study's main novelty lies in its operationalization of practical "diaconal engagement" and a lived "philosophy of encounter" within Christian higher education to transcend mere normative ideals. This research contributes to global discourses on peace education and moderating religious radicalism by providing a replicable matrix of scholastic leadership for multi-faith nations.